Synthesis and characterizations of sugar-glass nanoparticles mediated protein delivery system for tissue engineering application. Issue 2 (1st June 2022) - Pal, Aniruddha; Vel, Rathina; Rahaman, Sk Hasanur; Sengupta, Somoshree; Bodhak, Subhadip
Abstract: The present work focuses on the synthesis and characterization of a sugar-glass nanoparticle (SGnP) based reservoir type protein delivery system pertinent to tissue engineering applications. The SGnP nanocarriers were prepared via inverse micelle of sodium bis(2-ethylhexyl) sulfosuccinate based on an anionic surfactant and subsequent flash-freezing technique. Initially, a total of five different grades of protein-free SGnPs have been prepared to examine the effects of systematic changes in starting concentrations of the aqueous phase, organic solvent, the molar ratio of water, and surfactant in controlling the size, shape, and uniformity of micelles. Evidently, the Fourier transform infrared (FTIR) and scanning electron microscope (SEM) results confirmed that the SGnP can be successfully prepared. Subsequently, SGnP based protein depot has been validated using bovine serum albumin (BSA), horseradish peroxidase (HRP) and growth and differentiation factor-5 (GDF-5). The particle size, morphology, protein encapsulation efficiency and in vitro release kinetics were assessed using SEM, FTIR, UV–visible spectroscopy and Bradford protein assays. Excellent encapsulation efficiency (93%–94%) and sustained release behaviour of BSA (∼22% protein release after 14 d) and GDF-5 proteins (∼29% protein release after 30 d) were exhibited by the optimal grades of SGnP constructs with an average particle size of 266 nm and 93 nm, respectively. Furthermore, FTIR, differential scanning calorimeter (DSC), polyacrylamide gel electrophoresis (PAGE) and NATIVE-PAGE studies results confirm successful encapsulation, stability and preserving the structural integrity of proteins placed into the core of the SGnP constructs. Evidently, a very high (93%) residual HRP enzyme activity signifies the capability of our SGnP system to protect the encapsulated proteins from process-related stresses. In vitro cytotoxicity and fluorescence cell morphology analyses using human adipose-derived mesenchymal stem cells affirmed good cytocompatibility of protein encapsulated SGnP. Overall, the study findings indicate SGnP nanocarrier-mediated protein delivery systems as a promising approach complementary to conventional techniques in tissue engineering and therapeutic applications.